Comparison of Irradiation and Wolbachia Based Approaches for Sterile-Male Strategies Targeting Aedes albopictus. - Célestine M Atyame; Pierrick Labbé; Cyrille Lebon; Mylène Weill; Riccardo Moretti; Francesca Marini; Louis Clément Gouagna; Maurizio Calvitti; Pablo Tortosa (PLoS ONE, 2016)
The global expansion of Aedes albopictus together with the absence of vaccines for most of the arboviruses transmitted by this mosquito has stimulated the development of sterile-male strategies aiming at controlling disease transmission through the suppression of natural vector populations. In this context, two environmentally friendly control strategies, namely the Sterile Insect Technique (SIT) and the Wolbachia-based Incompatible Insect Technique (IIT) are currently being developed in several laboratories worldwide. So far however, there is a lack of comparative assessment of these strategies under the same controlled conditions. Here, we compared the mating capacities, i.e. insemination capacity, sterilization capacity and mating competitiveness of irradiated (35 Gy) and incompatible Ae. albopictus males at different ages and ratios under laboratory controlled conditions. Our data show that there was no significant difference in insemination capacity of irradiated and incompatible males, both male types showing lower capacities than untreated males at 1 day but recovering full capacity within 5 days following emergence. Regarding mating competitiveness trials, a global observed trend is that incompatible males tend to induce a lower hatching rate than irradiated males in cage controlled confrontations. More specifically, incompatible males were found more competitive than irradiated males in 5:1 ratio regardless of age, while irradiated males were only found more competitive than incompatible males in the 1:1 ratio at 10 days old. Overall, under the tested conditions, IIT seemed to be slightly more effective than SIT. However, considering that a single strategy will likely not be adapted to all environments, our data stimulates the need for comparative assessments of distinct strategies in up-scaled conditions in order to identify the most suitable and safe sterilizing technology to be implemented in a specific environmental setting and to identify the parameters requiring fine tuning in order to reach optimal release conditions.